Keynes's investment theory as a micro-foundation for his grandchildren - Sergio Nisticò (Kiel Institute for the World Economy (IfW), 2020)
In contrast with the "missing micro-foundations" argument against Keynes's macroeconomics, the paper argues that it is the present state of microeconomics that needs more solid "Keynesian foundations". It is in particular Keynes's understanding of investors' behaviour that can be fruitfully extended to consumption theory, in a context in which consumers are considered as entrepreneurs, buying goods and services to engage in time-consuming activities. The paper emphasizes that the outcome in terms of enjoyment is particularly uncertain for those innovative and path-breaking activities, which Keynes discussed in his 1930 prophetic essay about us, the grandchildren of his contemporaries. Moreover, the Keynes-inspired microeconomics suggested in the paper provides an explanation of why Keynes's prophecy about his grandchildren possibly expanding leisure did not materialize yet. The paper finally points at the need for appropriate economic policies supporting consumers' propensity to enforce innovative forms of time use.
Keywords: B41; D11; D81; 330; Keynesian microeconomics; consumption; time use; uncertainty; Keynes's grandchildren